Evaluation of compressive behavior of ultra-lightweight cement composite after elevated temperature exposure. (1st September 2017) - Huang, Zhenyu; Liew, J.Y. Richard; Li, Wei
Highlights: Residual mechanical properties of novel ULCC are reported. New test data for ULCC after elevated temperature exposure to 1000 °C are reported. No spalling of ULCC has been found after exposure to high temperature of 1000 °C. ULCC with small amount PVA fiber exhibits promising fire resistance. Abstract: This paper investigates the mechanical behavior of a new type of ultra-lightweight cement composite (ULCC) with density less than 1400 kg/m 3 and strength up to 60 MPa after exposing to elevated temperature up to 1000 °C. The residual compressive strength, elastic modulus, weight loss, failure modes and stress-strain curve behavior are studied experimentally. The heated specimens are explored both at macro and micro scales to investigate the physical behavior deterioration, color changes, cracking and spalling of ULCC at various temperatures. Chemical deterioration behavior is analyzed through XRD analysis and interfacial zone changes in ULCC matrix is examined by SEM observations. It is found that the ULCC containing high volume cenospheres and small amount of PVA fiber (0.2% and 0.5% in volume) exhibits promising thermal resistance compared to normal lightweight aggregate concrete and normal concrete of similar strength. The strength reduction rate and level of ULCC at elevated temperatures is smaller. Based on the test data, this paper proposes empirical equations to calculate the residual compressive strength and elastic modulus. Knowledge extracted from the experimental findings in this paper provides better understanding of the fundamental mechanical behavior of novel ultra-lightweight cement composite material after exposure to elevated temperature, which is helpful to develop design guide for fire resistance design of lightweight cement composite structures in the future.